Optimasi Pengelolaan Air Berkelanjutan di Perguruan Tinggi – Studi Kasus Institut Teknologi Bandung (Kampus Ganesha) - Dewi, Yulianty Kusuma (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Sustainable water management is crucial to tackle global challenges related to the depletion of Natural Resources and climate change. Universities becomes a driving factor in the development of knowledge. Assessment and evaluation of sustainable water management at the university is necessary to formulate recommendations for optimizing sustainable water management. The purpose of this study was to assess the score of implementation of sustainable water at the Institut Teknologi Bandung (ITB) using the UI (University of Indonesia) GreenMetric questionnaire, identify driving and inhibiting factors in implementing the concept of sustainable water management, and provide recommendations for the implementation of sustainable water management to run optimally. Data was collected by interviews, observations, field measurements, and questionnaires, with analysis conducted using the UI GreenMetric assessment methods and the Analytical Hierarchy Process (AHP). The findings revealed that ITB scored 550 out of 1,000 in sustainable water management practices. The role and authority of stakeholders influence the driving factor, for the inhibiting factors are limited funds, land, and conventional technology. Recommendations for implementing sustainable water within the university scope include financial analysis NPV and BCR, stakeholder training, feasibility studies, policy advocacy, water safety plan implementation, and rainwater harvesting technology application.